1998
DOI: 10.1016/s0022-5347(01)63948-x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Microwave Thermotherapy for Benign Prostatic Hyperplasia: Clinical Outcome After 4 Years

Abstract: Four years after transurethral microwave thermotherapy 23% of the initially treated group were satisfied with the result. Two-thirds had received supplementary BPH treatment. Preoperatively less obstructed patients and those with low initial irritative scores responded more favorably to transurethral microwave thermotherapy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 31 publications
3
33
1
2
Order By: Relevance
“…Comparable data were reported by Hallin and Berlin [11]who followed 187 patients for up to 4 years. Only 23% of the initially treated group were satisfied with the treatment outcome and two thirds had received supplementary BPH treatment [11]. Keijzers et al [12]reported on the 5–year follow–up data of 231 patients following low–energy TUMT.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Comparable data were reported by Hallin and Berlin [11]who followed 187 patients for up to 4 years. Only 23% of the initially treated group were satisfied with the treatment outcome and two thirds had received supplementary BPH treatment [11]. Keijzers et al [12]reported on the 5–year follow–up data of 231 patients following low–energy TUMT.…”
Section: Discussionsupporting
confidence: 70%
“…Within 3 years, 31% of the patients had to undergo TURP and a further 23% received medical therapy [9]. Comparable data were reported by Hallin and Berlin [11]who followed 187 patients for up to 4 years. Only 23% of the initially treated group were satisfied with the treatment outcome and two thirds had received supplementary BPH treatment [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations